Situation Report: Czechoslovakia, 25 March 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Munich Agreement and the Forthcoming West German-Czechoslovak Talks "Trotskyites" Sentenced University Students: Class Origin Important Again Book Month Traffic Problems in Prague and the Planned Subway